New approaches to the study of Antarctic lithobiontic microrganisms and their inorganic traces, and their application in the detection of life in Martian rocks - Ascaso, C.; Wierzchos, Jacek (International Microbiology, 2016)
Microbial life in the harsh conditions of Antarctica’s cold desert may be considered an analogue of potential life on early Mars. In order to explore the development and survival of this epilithic and endolithic form of microbial life, our most sophisticated, state-ofthe- art visualization technologies have to be used to their full potential. The study of any ecosystem requires a knowledge of its components and the processes that take place within it. If we are to understand the structure and function of each component of the microecosystems that inhabit lithic substrates, we need to be able to quantify and identify the microorganisms present in each lithobiontic ecological niche and to accurately characterize the mineralogical features of these hidden microhabitats. Once we have established the techniques that will allow us to observe and identify these microorganisms and mineral substrates in situ, and have confirmed the presence of water, the following questions can be addressed: How are the microorganisms organized in the fissures or cavities? Which microorganisms are present and how many are there? Additional questions that logically follow include: What are the existing water relationships in the microhabitat and what effects do the microorganisms have on the mineral composition? Mechanical and chemical changes in minerals and mineralization of microbial cells can give rise to physical and/or chemical traces (biomarkers) and to microbial fossil formation. In this report, we describe the detection of chains of magnetite within the Martian meteorite ALH84001, as an example of the potential use of SEM-SEMBSE in the search for plausible traces of life on early Mars. This study was funded by grant number ANT99-0680-C02-02 of the Plan Nacional I+D and BOS2000–1121 from the PGC.